Knowledge towards childhood immunization among mothers & reasons for incomplete immunization - Vinodkumar Mugada,Srujana Chandrabhotla,Divya Sai Kaja,Satya Gopala Krishna Machara (Journal of Applied Pharmaceutical Science, 2017)
The purpose of the present study was to determine the mother’s knowledge towards childhood immunization and examining the reasons for incomplete immunization. Information regarding socio demographic variables, gender disparity ratio, urban and rural inequality ratio and causes for incomplete immunization, knowledge of immunization was collected from 377 mothers bearing children of age 3 years. Around 115 (30.50%) children were partially immunized. Unavailability of vaccine was considered to be the major reason for incomplete immunization. The association between gender and immunization status (p=0. 027), mother’s education and knowledge score (p=0. 005) and area of residence and knowledge score towards immunization (p=0. 001) was found to be statistically significant. Mother’s education and area of residence were found to get associated with knowledge of immunization. However, knowledge towards immunization and immunization status was not significantly associated. Gender disparity in immunization was observed in the present study. No association was found between the children’s immunization status and area of residence, birth order or mother’s education. Area of residence and mother’s education and was found to get associated with knowledge of immunization.
Keywords: Immunization,Knowledge,gender disparity ratio,incomplete immunization.